Descriptive Study Evaluating Nurses Knowledge and Practices Regarding Tracheostomy Care in ICU Patients. - Adeeba Khanum, Gulzareen, Mubeen Owais, Ghulam Fizza, Farhat Miran Buksh, Samina Nazir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: ICU patient tracheostomy care is a fundamental nursing procedure. The tracheostomy might result in difficulties and causes a great deal of anxiety in patients. A low level of care can have negative consequences such as longer hospital stays, slower recovery times, and greater mortality rates. Aim: To evaluate nurses’ tracheostomy care knowledge and practises in ICU patients. Study Design: The descriptive research study design was used. Methodology: 75 nurses who worked in the ICU of three public hospitals in Lahore—Mayo Hospital, Jinnah Hospital, and Shaikh Zayed Hospital—were included in the study’s sample. Nurses’ practises were assessed by direct observation using a checklist, and their knowledge was assessed using a self-structured questionnaire. The analysis of the data was done using SPSS v 20.0. Results: All participants in the study were ICU nurses. This data makes clear that 0 - 49% of nurses have low knowledge, while 50 - 64% of nurses have average knowledge, and >65% of nurses have adequate knowledge. Conclusion: The majority of participants had sufficient understanding of tracheostomy care. Additionally, it demonstrates that out of 75 nurses, only 0–59% had insufficient skill and > 60% had a sufficient level of performance. Practical Implementation: This study assisted researchers in examining the risk variables related to Tracheostomy treatment in ICU patients because of the increasing number of patients in the ICU. Conclusion: It was concluded that, despite having sufficient information, nurses performed poorly when providing tracheostomy care. Therefore, for the safety of patients, health care facilities must provide organized clinical guidelines and practices. Keywords: Assessment, Knowledge, Practice, Nursing Care and Tracheostomy